Economic Drivers of Renewable Energy Growth in the European Union: Evidence from a Panel Data Analysis (2015–2023) - László Török (Energies)
The European Union (EU)’s climate policy and energy strategy objectives focus on increasing the share of renewable energy sources to reduce greenhouse gas emissions, strengthen energy independence, and achieve sustainable economic transformation. This study empirically examines to what extent and in what direction the GDP per capita, investment rate, and energy intensity influenced the development of the share of renewable energy sources in the 27 Member States of the European Union from 2015 to 2023. This research used multiple linear regression, β-convergence analysis, and a fixed-effects panel model to process panel data from official Eurostat databases. The results show that the effect of GDP per capita is structurally positive but not significant in terms of change within a particular country over time. In contrast, the investment rate is positively and significantly related to the share of renewable energy in all models. The results of the fixed-effects model highlight that in years when the investment rate in a given Member State increased, the share of renewable energy sources in gross final energy consumption also typically increased. In the case of energy intensity, no significant relationship was found. However, the literature suggests that improving energy efficiency continues to play a key role in achieving the EU’s sustainability goals. This study concludes that stimulating investment activity and developing country-specific energy strategies in the EU Member States are essential to accelerating the energy transition.